2013
DOI: 10.1007/s10463-013-0423-z
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics of the Empirical Cross-over Function

Abstract: We consider a combination of heavily trimmed sums and sample quantiles which arises when examining properties of clustering criteria and prove limit theorems. The object of interest, which we call the Empirical Cross-over Function, is an L-statistic whose weights do not comply with the requisite regularity conditions for usage of existing limit results. The law of large numbers, CLT and a functional CLT are proven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Let us start with the functional limit theorem for U n (p) = √ n(G n (p) − G(p)) proved in Bharath, Pozdnyakov and Dey (2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us start with the functional limit theorem for U n (p) = √ n(G n (p) − G(p)) proved in Bharath, Pozdnyakov and Dey (2012).…”
Section: Resultsmentioning
confidence: 99%
“…From a statistical perspective, we would like to work with the empirical version of (2.3). We deviate here from Hartigan's framework and consider the empirical cross-over function(ECF), defined in Bharath, Pozdnyakov and Dey (2012) as…”
Section: Empirical Cross-over Function and Empirical Split Pointmentioning
confidence: 99%
“…It is noted in Bharath et al [2013a] that the ECF G n is an L-statistic with irregular weights and hence not amenable for direct application of existing asymptotic results for L-statistics. Observe that…”
Section: Empirical Cross-over Functionmentioning
confidence: 99%
“…The index k at which this change occurs determines the datum W (k) at which the split occurs. In Bharath et al [2013a], it is shown that G n (p) is a consistent estimator of G(p) for each 0 < p < 1 and a functional CLT was also proved for…”
Section: Empirical Cross-over Functionmentioning
confidence: 99%
See 1 more Smart Citation